Nuclear position dictates DNA repair pathway choice - Lemaître, Charlène (Genes Dev, 2014)
Faithful DNA repair is essential to avoid chromosomal rearrangements and promote genome integrity. Nuclear organization has emerged as a key parameter in the formation of chromosomal translocations, yet little is known as to whether DNA repair can efficiently occur throughout the nucleus and whether it is affected by the location of the lesion. Here, we induce DNA double-strand breaks (DSBs) at different nuclear compartments and follow their fate. We demonstrate that DSBs induced at the nuclear membrane (but not at nuclear pores or nuclear interior) fail to rapidly activate the DNA damage response (DDR) and repair by homologous recombination (HR). Real-time and superresolution imaging reveal that DNA DSBs within lamina-associated domains do not migrate to more permissive environments for HR, like the nuclear pores or the nuclear interior, but instead are repaired in situ by alternative end-joining. Our results are consistent with a model in which nuclear position dictates the choice of DNA repair pathway, thus revealing a new level of regulation in DSB repair controlled by spatial organization of DNA within the nucleus.